2014
DOI: 10.1017/s0022215114000863
|View full text |Cite
|
Sign up to set email alerts
|

No association between obesity and post-tonsillectomy haemorrhage

Abstract: Overweight or obesity did not increase the risk of post-tonsillectomy haemorrhage in either children or adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 16 publications
3
21
0
Order By: Relevance
“…Our study did not shown a positive correlation between weight‐for‐age percentile and occurrence of post‐tonsillectomy hemorrhage, similar to the previously mentioned study performed in Austria . However, ours is the first to demonstrate a lack of correlation in a primarily overweight and obese population, with a median weight‐for‐age percentile of 75.26%.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our study did not shown a positive correlation between weight‐for‐age percentile and occurrence of post‐tonsillectomy hemorrhage, similar to the previously mentioned study performed in Austria . However, ours is the first to demonstrate a lack of correlation in a primarily overweight and obese population, with a median weight‐for‐age percentile of 75.26%.…”
Section: Discussionsupporting
confidence: 86%
“…To the authors’ knowledge, there has been only one study, from Austria, researching this association, wherein no association between obesity and PTH was found. However, their study, in a country where only 12% of the adult and 7% of the children populations are obese, included both children and adults …”
Section: Introductionmentioning
confidence: 99%
“…In contrast to this finding, a previous report showed that overweight or obesity did not increase the risk for PTH [15]. The reason for this discrepancy between studies is unclear.…”
Section: Discussionmentioning
confidence: 57%
“…This BMI classification system is endorsed by the World Health Organization and the National Institutes of Health. This system is the most widely accepted means of stratifying individuals based on weight [15]. Patients with hematological diseases, deteriorated immune function, chronic wasting disease, and uncontrolled chronic disease were excluded.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation